Single-cell RNA sequencing revealed cell heterogeneity in sagittal suture mesenchyme - Ren, Chengyan; Sun, Kai; Wu, Ran; Geng, Chenxin; Chen, Jiangping; Zhao, Hu; Chen, Weihui (Frontiers in Cell and Developmental Biology, 2026)
IntroductionThe formation and homeostatic maintenance of cranial sutures rely on cellular activities within the suture mesenchyme. However, how mesenchymal stem/stromal cells (MSCs) rapidly and extensively contribute to suture and cranial development remains insufficiently explored.MethodsWe integrated 10x Genomics and Smart‐seq3 single‐cell transcriptomic sequencing to analyze cellular subpopulations in the sagittal suture mesenchyme. CytoTRACE2 analysis was performed to quantitatively assess the differentiation status of each cell population. We further characterized the progenitor with characteristics of transient amplifying cells (TACs) via 5‐ethynyl-2’‐deoxyuridine (EdU) assays, in situ hybridization, and lineage tracing using Ki67CreERT2;tdTomato mice. Through bioinformatics analysis based on sequencing data, we filtered transcription factors of key cell populations.ResultsSmart‐seq3 showed higher sequencing depth and improved capture efficiency for target cell populations. Then, we identified a proliferative progenitor population in the sagittal suture that exhibited features of TACs. These TACs were a committed, proliferative direct lineage of suture mesenchymal stem/stromal cells (SuSCs) and responsible for rapid development of cranial structures. Additionally, Erg and E2f7/8 were expressed in SuSCs and TACs, respectively. Among these, Erg downstream targets participated in biological processes governing MSCs and bone morphogenesis processes, while E2f7/8 downstream targets primarily regulate the cell cycle.DiscussionThis study provides the first identification of TACs within the developing cranial suture niche and elucidates key regulatory genes and signaling networks in SuSCs and TACs, thereby providing a theoretical framework for understanding the mechanisms underlying cranial suture formation and homeostasis.